Adjunctive therapy in Parkinson's disease: the role of rasagiline - Gaines KD (Dove Medical Press, 2012)
Kathryn D Gaines,1 Vanessa K Hinson21Department of Neurology, Aurora Advanced Healthcare, Milwaukee, WI, 2Department of Neurosciences, Movement Disorders Program, Medical University of South Carolina, Charleston, SC, USAAbstract: Parkinson's disease is the second most common neurodegenerative disorder, currently affecting 1.5 million people in the US. In this review, we describe the diagnostic and pathological features of Parkinson's disease, as well as its clinical course. We then review pharmacologic treatments for the disease, with a particular focus on therapies adjunctive to levodopa and specifically the role of rasagiline. We review the four pivotal rasagiline trials, and discuss rasagiline and its use as adjunctive therapy for Parkinson's disease. Finally, we discuss potential side effects, drug interactions, and other practical aspects concerning the use of rasagiline in Parkinson's disease.Keywords: Parkinson's disease, treatment, rasagiline, clinical trials